2007
DOI: 10.1007/s00421-007-0645-y
|View full text |Cite
|
Sign up to set email alerts
|

Local differences in sweat secretion from the head during rest and exercise in the heat

Abstract: The importance of the head in dissipating body heat under hot conditions is well recognised, although very little is known about local differences in sweat secretion across the surface of the head. In this study, we focused on the intra-segmental distribution of head sweating. Ten healthy males were exposed to passive heating and exercise-induced hyperthermia (36 degrees C, 60% relative humidity, water-perfusion suit: 46 degrees C), with ventilated sweat capsules (3.16 cm(2)) used to measure sweat rates from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 20 publications
3
50
2
Order By: Relevance
“…In general, sweat gland densities are higher at the forehead, hand and foot, and lower on the thigh and leg, with the arms and trunk displaying intermediate densities (Thompson 1954;Szabo 1962Szabo , 1967Knip 1969;Hwang and Baik 1997). A caudalto-rostral pattern of sweat onset has been demonstrated for resting subjects (Randall and Hertzman 1953), with higher thermal sweat secretions usually observed at the forehead during resting and exercising states (Cotter et al 1995;Machado-Moreira et al 2007b). These generalisations are well accepted, but there is a paucity of knowledge concerning diVerences in sweat secretion within body segments.…”
Section: Introductionmentioning
confidence: 93%
“…In general, sweat gland densities are higher at the forehead, hand and foot, and lower on the thigh and leg, with the arms and trunk displaying intermediate densities (Thompson 1954;Szabo 1962Szabo , 1967Knip 1969;Hwang and Baik 1997). A caudalto-rostral pattern of sweat onset has been demonstrated for resting subjects (Randall and Hertzman 1953), with higher thermal sweat secretions usually observed at the forehead during resting and exercising states (Cotter et al 1995;Machado-Moreira et al 2007b). These generalisations are well accepted, but there is a paucity of knowledge concerning diVerences in sweat secretion within body segments.…”
Section: Introductionmentioning
confidence: 93%
“…Reliability was assessed during pilot tests and whilst some variations did exist the response to a given condition was similar. The large variation in individual sweat gland output may accounts for the variation seen in GSC but also in that from other studies when measuring sweat (Smith & Havenith, 2011, 2012Cotter et al 1995;Machado-Moreira et al 2008). Standardising the value relative to a baseline value aimed to reduce these errors but the high dispersion of values reduces the certainty of predicting thermal discomfort using GSC as can be seen in Table 3 and 4.…”
Section: A Comparison Of W Local and δGsc In Predicting Thermal Discomentioning
confidence: 98%
“…The ventilated capsule (7.1 cm 2 ) was fixed to the upper section of the left scapula and the local sweat rate (LSR vc ) was measured during the exercise by using the ventilated capsule method [3][4][5][6][7][10][11][12][13]15,16] After the exercises, a part of the absorbent pad was pulled out from each of the tailored pads fixed on the skin. Each absorbent pad was quickly placed, separately, into an impermeable plastic Ziploc bag and weighed with the bag.…”
Section: Studymentioning
confidence: 99%
“…Previous studies of regional sweat rates found that the local sweat rate (LSR) clearly varies among the different body sites [1][2][3][4][5][6], and that LSR on the forehead and torso was greater than that of the limbs [1][2][3][4]. Some studies have focused on the differences in sweat regulation depending on maturation and aging [7][8][9][10][11], sex [12,13], fitness [8,14,15], and heat acclimation [8,16] to elucidate the mechanism underlying thermoregulation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation